The European Network Against Racism (ENAR) as NGO Against Islamophobia in France - ILMISANI, Radendy Ahmad; JUNED, Mansur (PT Keberlanjutan Strategis Indonesia, 2024)
This research, will explain about the relationship between the European Network Against Racism (ENAR) and Islamophobia in France. The increasing Muslim population in France over the years, driven by globalization and immigration, is a significant aspect to consider. While their freedoms should be preserved, the challenging reality in France is the difficulty in upholding these rights due to Islamophobia within the majority of the French population and institutional racism (with France Laïcité) that diminishes their chances of obtaining their rights. Therefore, employing a case study data collection technique, this study will explore how ENAR, as a Non-Governmental Organization, takes action to address this issue through projects such as